2002
DOI: 10.1053/rmed.2001.1335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formoterol (Oxis® Turbuhaler®) and ipratropium on exercise capacity in patients with COPD

Abstract: Although long-acting inhaled beta 2-agonists improve various outcome measures in COPD, no double-blind study has yet shown a significant effect of these drugs on exercise capacity. In a randomized, double-blind, placebo-controlled, crossover study, patients received formoterol (4, 5, 9, or 18 micrograms b.i.d. via Turbuhaler), ipratropium bromide (80 micrograms t.i.d. via pMDI with spacer), or placebo for 1 week. Main endpoint was time to exhaustion (TTE) in an incremental cycle ergometer test. Secondary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…In Europe, studies have shown formoterol to have beneficial effects at dosages of 4.5, 9 and 18 μg twice daily (bid) in patients with COPD (9,10). However, the effects of formoterol on lung functions and symptoms have never been investigated in Japanese patients with COPD.…”
Section: Copd Is a Disease State Characterized By The Presence Of Chrmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, studies have shown formoterol to have beneficial effects at dosages of 4.5, 9 and 18 μg twice daily (bid) in patients with COPD (9,10). However, the effects of formoterol on lung functions and symptoms have never been investigated in Japanese patients with COPD.…”
Section: Copd Is a Disease State Characterized By The Presence Of Chrmentioning
confidence: 99%
“…assuming that the standard deviation of log-transformed FEV1 was 0.10 (9). Allowing for withdrawals, a total of 37 patients was the target sample size for randomization in this study.…”
Section: F I G U R E 1 F L O W D I a G R A M O F P A T I E N T D I mentioning
confidence: 99%
“…16,17 Furthermore, these effects seem to be dose dependent; formoterol improves lung function parameters with a positive dose-response relationship and exercise capacity with a negative relationship, probably because increased unevenness in ventilation-perfusion ratio at higher doses limits exercise capacity. 29 This study had several limitations. First, the relatively small sample size and the short period between dosing and measurements likely increased the threshold for some changes (eg, VAS results) achieving significance after the administration of formoterol.…”
Section: Discussionmentioning
confidence: 93%
“…Long-acting beta-agonists such as salmeterol and formoterol have been shown to decrease resting and dynamic hyperinflation and increase exercise performance [120][121][122][123][124], although this improvement did not always reach clinical significance. Indacaterol, tiotropium, glycopyrronium bromide and aclidinium bromide also showed their ability to positively impact hyperinflation and improve exercise capacity [92,[125][126][127][128][129][130][131][132][133].…”
Section: Treatmentmentioning
confidence: 99%